2018
DOI: 10.1093/ecco-jcc/jjy080
|View full text |Cite
|
Sign up to set email alerts
|

An Intergenic Variant rs9268877 Between HLA-DRA and HLA-DRB Contributes to the Clinical Course and Long-term Outcome of Ulcerative Colitis

Abstract: Our results provide new insights into prognosis-associated genetic variation in UC, which appears to be distinct from the genetic contribution to disease susceptibility. These findings could be useful in identifying poor-prognosis patients who might benefit from early aggressive therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Genetic and environmental factors may play roles. Although the genetic associations for UC overlap more extensively between Asian patients and patients of European ancestry than those for CD, the difference in the clinical course between these populations is more prominent in UC than in CD 30. However, this does not necessarily indicate that environmental factors are more important than genetic factors in determining the prognosis of UC versus that of CD.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Genetic and environmental factors may play roles. Although the genetic associations for UC overlap more extensively between Asian patients and patients of European ancestry than those for CD, the difference in the clinical course between these populations is more prominent in UC than in CD 30. However, this does not necessarily indicate that environmental factors are more important than genetic factors in determining the prognosis of UC versus that of CD.…”
Section: Discussionmentioning
confidence: 95%
“…Even among East Asians, the proportion of proctitis is higher in Koreans than in Chinese 6 12. With respect to the genetic predictors of UC prognosis, the intergenic variant rs9268877 between HLA-DRA and HLA-DRB has been reported to be associated with a poor prognosis of UC in Koreans 30. However, this association is yet to be reported in other Asian populations.…”
Section: Discussionmentioning
confidence: 98%
“…A recent Korean study identified HLA‐DRB4*01:01 as a risk genotype for ulcerative colitis, however this allele was in strong linkage disequilibrium with a SNP, rs9268877, lying between the HLA‐DRA and DRB genes . Following correction for this genotype, rs9268877 was the strongest risk signal and conferred an increased risk of severe disease with poor outcome (OR 1.72) …”
Section: Specific Associations: Hla and Ibdmentioning
confidence: 99%
“…Using a similar approach, Kopylov et al found that none of their studied susceptibility loci were associated with benign UC [44]. In East Asians with UC, the SNP located between HLA-DRA and HLA-DRB (rs9268877) was found to be associated with a poor prognosis but not with susceptibility [45]. These studies highlight the need for detailed clinically relevant sub-phenotypes and categorization by relevant clinical outcomes in IBD.…”
Section: The Predictability Of Ibd Disease Progressionmentioning
confidence: 99%
“…Although IBD patients tend to have larger average PRS than non-IBD individuals, this has not produced substantial improvements in predicting their clinical course. Indeed, no associations could be shown between genetic burden and development of complicated disease or need for surgery [39,42,44,45,46,47].…”
Section: The Predictability Of Ibd Disease Progressionmentioning
confidence: 99%